PENGENALAN BAHASA INGGRIS MELALUI MEDIA AUDIO-VISUAL BAGI SISWA TK MARIA VIRGO 2 ENDE - Maksimilianus Doi; F. F. Irawati Wanggai; Marianus Woda Liru (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
This Community Service Activity aimed at introducing English to young children as beginners through audio-visual media. The learning media was implemented audio-visually with 15 students at TK Maria Virgo 2 Ende. The methods used were two phases, namely preparation and implementation phases. During the learning process, learning materials were presented in the form of videos displayed in LCD regarding alphabeth, colors, and numbers. The results of this program show that the process of introducing English is very enjoyable and students are able to follow it well.